Implementasi Model Direct Instruction Dalam Pembelajan Bola Basket di SMAN 1 Ciasem - Cantika Febriyanti; Abdulloh Abdulloh; Dhika Bayu Mahardhika (Peneliti.net, 2022)
The purpose of this study was to improve basketball learning outcomes in class XI students in the 2022/2023 academic year in physical education subjects using the implementation of the direct instruction model. This research is a qualitative descriptive study using data collection techniques using interview instruments. In this study, the subjects were 1 physical education teacher at SMAN 1 Ciasem and 5 students from each representative of class XI. From the results of the study it can be concluded that the implementation of the direct instruction model can improve student learning outcomes in physical education subjects, especially in basketball material because the direct instruction model requires the teacher to explain in detail the material being taught and carried out in a step-by-step manner so that students can understand what has been explained and practiced by the teacher.